ANALYSIS OF THE MANAGEMENT INDICATORS OF THE MOBILE EMERGENCY CARE SERVICE OF CEARÁ - Natália Pinheiro Fabricio Formiga; Lucilane Maria Sales da Silva; José Hiago Feitosa de Matos; Emiliana Bezerra Gomes; Kelly Fernanda Silva Santana; Francisco Edilson Ferreira; Maria Veraci Oliveira Queiroz (Universidade Federal do Paraná, 2023)
Objective: To analyze the health management indicators related to the mobile emergency care service in Ceará. Method: This is a documentary, retrospective, quantitative study, carried out on the IntegraSUS website of the Ceará state government - Brazil, during the period July 2021, to analyze the indicators "total calls" and "average response time". Results: It was verified a profile of prevalent calls for men (52.66%), with advanced age >70 years (22.06%), Covid-19 service occurrences for the Juazeiro central station (7.62%) and motorcycle accidents for the Eusébio central station (7.94%). The service got calls for 177 cities in Ceará (96.19%) with a longer average response time for Covid-19. Conclusion: The analysis signals the need to adjust strategies to improve the performance of the service response time, with a review of the organizational system, including the publication of data by the digital platform.